Die voorspelling van gevaarlikheid: 'n psigoforensiese studie - Strydom, Christoffel Cornelius (University of the Free State, 2004)
The prediction of dangerousness, more recently known as risk management, has become an integral part of the criminal justice system. The purpose of these predictions is to make an significant contribution in the prevention of violent crime. Although predictions of this nature as well as research on this fenomenon have been around on the international scene for more than two decades, almost nothing has been done in this regard in South Africa. This is especially distressing because of the current violent crime rate in this country and specifically because of the detrimental effect it has on the victims and their families, the community at large and the country as a whole politically, financially and mental healthwise. Significant reduction of violent crime, also through effective predictions, should be seen as a national priority The main purpose of this study was to alleviate the apparent lack of research in South- Africa on the prediction of dangerousness; more specifically, to identify the criteria which the involved professionals (i.e. magistrates and psychologists), use when determining dangerousness. A secondary purpose was to test the respondents on several related matters (eg. prejudice, training and the most effective sentencing) when sentencing of violent crime is considered. The perceptions of the involved role players were obtained through a self compiled questionnaire. Answers to specific questions concerning dangerousness and related forensic aspects, and evaluating of fictional case studies, were where applicable, amplified by qualitative comment. The core findings were the following: - the most important violence predicting criteria identified by both respondent-groups, were: repeated exposure to violence, a history of violent conduct, threats to commit violence and (to a limited extent), a history of treatment of certain psychiatric disorders; - the occupational groups differed in the emphasis that was placed on certain risk factors (eg. psychologists accentuated factors like age, sex, absence of violent history and remorse, more than the lawyer-group did); and - the views of the psychologists on psycho-forensic aspects relating to sentencing of violent offenders, were more supported by empirical research, than the opinions of the magistrates. It is specifically recommended that research on the effective prediction of violent behaviour be done on an ongoing basis and that it should receive national priority and funding.

Die voorspelling van gevaarlike, oftewel gewelddadige gedrag, tans ook bekend as geweldrisiko-bestuur, het 'n wesenlike deel van die kriminele regspleging wêreldwyd geword. Die doel van sodanige voorspellings is uiteraard om 'n betekenisvolle bydrae te maak tot die bekamping van geweldsmisdade. Hoewel geweldvoorspelling en navorsing oor geweldvoorspelling internasionaal reeds vir meer as twee dekades hoë prioriteit geniet, bestaan daar 'n skreiende tekort in dié verband in Suid-Afrika. In die lig van die onaanvaarbaar hoë geweldmisdaadkoers hier te lande, is hierdie toedrag van sake des te meer kommerwekkend aangesien geweldmisdade die slagoffers sowel as die land op feitlik alle terreine onberekenbare skade aandoen. Gevolglik behoort die bekamping van geweldsoortredings en veral metodes wat daartoe meehelp, soos die voorspelling van gewelddadige gedrag, die hoogste nasionale prioriteit te geniet. Die kerndoelstelling met die onderhawige studie was om die gebrek aan navorsing oor geweldvoorspelling in Suid-Afrika uit te wys; meer spesifiek om die kriteria te identifiseer aan die hand waarvan regslui en sielkundiges gewelddadige gedrag kan voorspel. 'n Sekondêre doelwit was om die twee beroepsgroepe se menings te loets oor aspekte van psigo-forensiese werk wat verband hou met die straftoemeting van geweldsmisdade soos opleiding, subjektiwiteit en effektiewe strafbepaling. Die standpunte en sienings van die betrokke respondentgroepe is met behulp van 'n selfopgestelde vraelys verkry. Die beantwoording van bepaalde vrae oor gewelddadige gedrag, evaluering van geweldpotensiaal by 'n aantal fiktiewe gevallestudies en ander verbandhoudende psigoforensiese kwessies, is waar dit van toepassing was, met kwalitatiewe toeligting aangevul. Die belangrikste bevindings was dat - beide beroepsgroepe dieselfde geweldvoorsp.ellende faktore as deurslaggewend beskou het naamlik, herhaaldelike blootstelling aan geweld, 'n geweldsgeskiedenis, geweldsdreigemente, en (met bepaalde voorbehoude) 'n geskiedenis van psigiatriese behandeling; - die regslui en sielkundiges verskil het ten opsigte van die waarde wat aan bepaalde risikofaktore toegeken is. Die sielkundiges het byvoorbeeld veranderlikes soos geslag, ouderdom en die afwesigheid van 'n misdaadrekord, meer beklemtoon as die regslui; - die menings van die sielkundiges oor watter psigo-forensiese faktore 'n belangrike rol speel by straftoemeting by geweldsoortredings, meer deur empiriese navorsing ondersteun word as dié van die regslui. Daar word veral aanbeveel dat hierdie navorsing nie slegs op 'n deurlopende en professionele basis moet voortgaan nie, maar ook dat dit nasionaal dringende en statutêre aandag behoort te geniet.
Thesis (Ph.D. (Psychology))--University of the Free State, 2004
Keywords: Prediction of dangerousness; Violence prediction; Violence assessment; Risk management; Risk assessment; Risk markers; Violence -- Forecasting; Criminal behavior, Prediction of; Violent crimes